Effect of relative humidity decrease due to self-desiccation on the hydration kinetics of cement. (July 2016) - Wyrzykowski, Mateusz; Lura, Pietro
Abstract: Hydration rate of cement decreases at reduced relative humidity (RH) and hydration virtually ceases below about 80% RH. Until now, this problem has been studied by means of determining the hydration degree only at later ages on hydrated samples continuously stored under fixed, reduced RH, or based on theoretical considerations. Here, the effect of reduced RH on hydration rate was studied in the course of the process during initial days of hydration. Isothermal calorimetry was applied to study the evolution of the heat of hydration in cement pastes with low water-to-binder ratio, either in water-saturated or sealed conditions. In parallel, RH evolution was measured on sealed, companion samples with water-activity stations. The sealed samples show considerably lower rates of hydration when the RH is reduced due to self-desiccation. The coefficient describing the reduction of hydration rate as a function of RH was determined for different water-to-binder ratios and different cements. Highlights: Differences in hydration kinetics between sealed and water-saturated cement pastes are studied with isothermal calorimetry. Effect of continuously reduced RH on hydration kinetics is quantified. Hydration rate reduces compared to water-saturated samples to 20–60% at 90% RH, with no clear trend regarding cement type or w/b. Hydration virtually ceases at about 80% RH for all tested cements and w/b.